Case Study: Intervensi Mengunyah Permen Karet Terhadap Penurunan Rasa Haus Pasien CHF - Arsyawina, Arsyawina; Munawarah, Nurul; Bua, Noviani; ⁠Maharani, ⁠Yusva; Sipasulta, Grace; Dortauli, Simanullang; Pinarsih, Pinarsih (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Objective : Heart failure is 85% of the causes of death in cardiovascular disease. There were 13 cases of CHF during the last 3 months in the RSKD ICCU. CHF patients often experience fluid overload which requires fluid restriction, causing thirst. One alternative to reduce thirst is by chewing gum. The aim is to analyze CHF patients with Chewing Gum Intervention to Reduce Thirst in the ICCU RSUD Dr.Kanujoso Djatiwibowo Balikpapan. Methods : The method used was descriptive analysis with a sample of 2 patients. Before the intervention was given, a TDS pre-test, then the intervention was given to chew gum for 10 minutes 6 times/3 days and a post-test. Results : In both patients, hypervolemia was found with symptoms, patient 1 complained of shortness of breath, thirst, edema of legs, ascites, while patient 2 complained of shortness of breath, cough, thirst, cardiomegaly accompanied by pulmonary edema. From the results it was found that the chewing gum intervention was able to reduce thirst with TDS in case 1 decreasing the score from 23 to 15 with a difference of 8, while in case 2 the score decreased from 19 to 14 with a difference of 5. Conclusion : There is an effect of chewing gum intervention on reducing thirst in CHF patients in the ICCU RSUD Dr. Hospital. Kanujoso Djatiwibowo Balikpapan. It is hoped that it can be a source of information, knowledge development and therapy in reducing thirst.